Blunt Renal Trauma - Dalton, Brian G. A.; Dehmer, Jeff J.; Shah, Sohail R. (Journal of Pediatric Intensive Care, 2015)
The pediatric patient is especially prone to blunt renal trauma due to the size and location of pediatric kidneys. No clear guidelines have been established for the management of these injuries in children to achieve the highest rate of renal salvage with low morbidity. Wide-ranging literature exists on this subject, but consists of vastly different management strategies. This review is written to summarize the different approaches to blunt renal trauma and highlight opportunities for further research.
Keywords: angioembolization; blunt renal trauma; kidney; nonoperative management; pediatrics